2016
DOI: 10.3390/ijms17081327
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Berberine on Renal Injury in Streptozotocin (STZ)-Induced Diabetic Mice

Abstract: Diabetic nephropathy (DN) is a serious diabetic complication with renal hypertrophy and expansion of extracellular matrices in renal fibrosis. Epithelial-to-mesenchymal transition (EMT) of renal tubular epithelial cells may be involved in the main mechanism. Berberine (BBR) has been shown to have antifibrotic effects in liver, kidney and lung. However, the mechanism of cytoprotective effects of BBR in DN is still unclear. In this study, we investigated the curative effects of BBR on tubulointerstitial fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 61 publications
2
40
0
Order By: Relevance
“…Evidence is available that BBR protects human renal proximal tubular cells from hypoxia/reoxygenation injury by inhibiting endoplasmic reticulum and mitochondrial stress 31. Zhang et al26 have recently demonstrated that BBR can ameliorate tubulointerstitial fibrosis in DN by activating the Nrf2 pathway and inhibiting TGF-β/Smad/EMT signaling activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence is available that BBR protects human renal proximal tubular cells from hypoxia/reoxygenation injury by inhibiting endoplasmic reticulum and mitochondrial stress 31. Zhang et al26 have recently demonstrated that BBR can ameliorate tubulointerstitial fibrosis in DN by activating the Nrf2 pathway and inhibiting TGF-β/Smad/EMT signaling activity.…”
Section: Discussionmentioning
confidence: 99%
“…After growing tô80% confluence, the mRTECs were cultured in serum-free DMEM for 24 h at 37°C to arrest and synchronize cell growth. In vitro, the cells were divided into the following four groups: 1) NG, in which the cells were treated with DMEM containing 5.5 mM/L glucose; 2) HG group, in which the cells were treated with 30 mM/L glucose; 3) BBR group, in which the cells were treated with 30 mM/L glucose and 30 μM BBR;26 and 4) DAPT group, in which the cells were treated with 30 mM/L glucose after pretreatment with 10 μM/L N -[ N -(3,5-difluorophenacetyl)- l -alanyl]- S -phenylglycine t -butyl ester (DAPT; Sigma-Aldrich, Darmstadt, Germany) for 40 min. The mRTECs of the four groups were treated for 48 h and then used for the purposed experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 6, berberine ameliorated renal inflammation and injury in diabetic models [79,83,85,86,90,96]. Underlying mechanisms include inhibition of kidney fibrosis via tumor growth factor (TGF)- signaling suppression and Nrf2 activity enhancement [76,77,80,82,86,91,93,144], suppression of HG-induced mesangial cell proliferation and hypertrophy via suppression of NF-B and AP-1 [81,84,90], and attenuation of ECM accumulation [87], possibly by restoring β-arrestin [88] and E prostanoid receptor 4 (EP4)-Gαs-cAMP signaling pathway [83,85]. In addition, berberine directly protected podocytes from HG-induced injury in vitro [23,94], possibly by inhibiting podocyte apoptosis via AMPK-dependent autophagy induction [92].…”
Section: Kidney Dysfunctionmentioning
confidence: 99%
“…In the context of renal fibrosis, [57]. Similarly, renal fibrosis in a variety of animal models were mitigated via TGF-β/Smad pathways by administration of natural products, such as GQ5 [58], curcumin [59,60], arctigenin [61], resveratrol [62], sinomenine [63], berberine [64,65], leonurine [66], rutin [67], bergenin [68], oxymatrine [69,70], oleanolic acid [71], tanshinone IIA [72], astragaloside IV [73,74], (+/-)sinensilactam A [75] and epigallocatechin-3-gallate [76]. Besides, inflammation could in the activation of immune cells, including macrophages, dendritic cells and T cells.…”
Section: Tgf-β/smad In Renal Fibrosismentioning
confidence: 99%